2008
DOI: 10.1152/jn.90759.2008
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Regulation of Network Components Underlying Ciliary Locomotion inHermissenda

Abstract: Crow T, Tian L-M. Sensory regulation of network components underlying ciliary locomotion in Hermissenda. J Neurophysiol 100: 2496 -2506, 2008. First published September 3, 2008 doi:10.1152/jn.90759.2008. Ciliary locomotion in the nudibranch mollusk Hermissenda is modulated by the visual and graviceptive systems. Components of the neural network mediating ciliary locomotion have been identified including aggregates of polysensory interneurons that receive monosynaptic input from identified photoreceptors and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This indicates that in addition to their contribution to the network supporting ciliary locomotion, type II interneurons are also involved in other light-dependent processes based on their anatomic projections and not differences in light responses. The spike activity of dark-adapted and light-adapted type II interneurons is tonic, which is consistent with the nonrhythmic spike activity of I e and I i interneurons recorded in the dark and during illumination (Crow and Tian 2008).…”
Section: Anatomic Diversity Of Type II Interneuron Projectionssupporting
confidence: 85%
See 4 more Smart Citations
“…This indicates that in addition to their contribution to the network supporting ciliary locomotion, type II interneurons are also involved in other light-dependent processes based on their anatomic projections and not differences in light responses. The spike activity of dark-adapted and light-adapted type II interneurons is tonic, which is consistent with the nonrhythmic spike activity of I e and I i interneurons recorded in the dark and during illumination (Crow and Tian 2008).…”
Section: Anatomic Diversity Of Type II Interneuron Projectionssupporting
confidence: 85%
“…Spike activity was examined in II e (n ϭ 10) and II i (n ϭ 10) interneurons before (dark adapted) and during 5 min of illumination of the eyes (light adapted) to characterize light responses under conditions of illumination supporting phototactic behavior. Previous results have shown that the spike activity of dark-adapted type I e and I i interneurons is characterized by a change in tonic firing with the generation of occasional irregular burst activity that is not repetitive or rhythmic (Crow and Tian 2008). Group summary data showing the mean spike frequency measured at consecutive 1-min periods, 5 min before light onset, during 5 min of light, and 5 min after light offset are shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations